POTENSI PASAR WISATAWAN CINA: PELUANG DAN TANTANGANNYA - I Wayan Mertha (JURNAL KEPARIWISATAAN, 2007)
Among the world tourist whos visit Bali, the Chinese could be another big potential market segment. Due to this opportunity, this paper tries to find out the characteristics of this market, proposes strategies to gain and analyses the exiting challenges. The conclusion is in the form of recommendation a reminder that Bali has huge, prospective visitors